Sudden arrhythmia followed by bradycardia during sagittal split ramus osteotomy: trigeminocardiac reflex. Issue 12 (2nd December 2019) - Kim, Hyunjee
Abstract : Trigeminocardiac reflex (TCR) is a brainstem reflex triggered by the stimulation of any branch of the fifth cranial nerve along its course, presenting as a reduction in heart rate and blood pressure. Oculocardiac reflex is a well-known subtype of TCR. In the case reported here, remarkable arrhythmia followed by bradycardia occurred suddenly in a healthy patient undergoing orthognathic surgery. The heart rhythm recovered when the surgical manipulation ceased, but bradycardia was reproduced when the surgery resumed. This case of TCR is unique in that remarkable arrhythmia first appeared and led to bradycardia; accordingly, intravenous lidocaine and an anticholinergic agent were administered simultaneously instead of anticholinergic agents alone, and were protective. Although TCR rarely occurs during orthognathic surgery, clinicians should be aware of its possibility and able to judge and manage it promptly.